RE-EQUILIBRATION OF MELT INCLUSIONS TRAPPED BY MAGNESIAN OLIVINE PHENOCRYSTS FROM SUBDUCTION-RELATED MAGMAS: PETROLOGICAL IMPLICATIONS - Danyushevsky L.V.; Della-Pasqua F.N.; Sokolov S. (My University, 2000)
We describe and model a potential re-equilibration process that can affect compositions of melt inclusions in magnesian olivine phenocrysts. This process, referred to as “Fe-loss”, can operate during natural pre-eruptive cooling of host magma and results in lower FeOt and higher MgO contents within the initially trapped volume of inclusion. The extent of Fe-loss is enhanced by large temperature intervals of magma cooling before eruption. The compositions of homogenised melt inclusions in olivine phenocrysts from several subduction-related suites demonstrate that (1) Fe-loss is a common process, (2) the maximum observed degree of re-equilibration varies between suites, and (3) within a single sample, variable degrees of re-equilibration can be recorded by melt inclusions trapped in olivine phenocrysts of identical composition. Our modelling also demonstrates that the re-equilibration process is fast going to completion, in the largest inclusions in the most magnesian phenocrysts it is completed within 2 years. The results we obtained indicate that the possibility of Fe-loss must be considered when estimating compositions of parental subduction-related magmas from naturally quenched glassy melt inclusions in magnesian olivine phenocrysts. Compositions calculated from glassy inclusions affected by Fe-loss will inherit not only erroneously low FeOt contents, but also low MgO due to the inherited higher Mg##of the residual melt in re-equilibrated inclusions. We also demonstrate that due to the higher MgO contents of homogenised melt inclusions affected by Fe-loss, homogenisation temperatures achieved in heating experiments will be higher than original trapping temperatures. The extent of overheating will increase depending on the degree of re-equilibration, and can reach up to 50°C in cases where complete re-equilibration occurs over a cooling interval of 200°C.